Determinants of maternal knowledge of neonatal danger signs among postpartum mothers in Southern Ethiopia: institutional-based cross-sectional study - Haimanot Abebe; Solomon Shitu; Ayenew Mose; Habtamu Shimels (BMJ Open)
Objective The main aim of this study was to assess knowledge of neonatal danger signs and associated factors among postpartum mothers in Southern Ethiopia.Setting Gurage zone, Southern Ethiopia.Study participants A total of 608 postpartum mothers were involved in this study.Methods An institutional-based cross-sectional study design was conducted among postpartum mothers attending Gurage zone public health facilities of Southern Ethiopia from 1 January 2020 to 30 January 2020.Results Knowledge of neonatal danger signs among postpartum mothers was 48.2% (95% CI 44.4% to 52.3%). Mothers resided in an urban area (adjusted OR, AOR=1.67, 95% CI 1.11 to 2.50), having antenatal follow-up (AOR=1.49, 95% CI 1.02 to 2.18), mothers who had got breastfeeding counselling (AOR=3.43, 95% CI 1.89 to 4.75), mothers who had got postnatal care counselling (AOR=1.53, 95% CI 1.08 to 2.18), multiparous mothers (AOR=1.37, 95% CI 1.24 to 2.19) and mothers who had good practice of essential newborn care (AOR=1.53, 95% CI 1.06 to 2.21) were factors significantly associated with maternal knowledge of neonatal danger signs.Conclusions Knowledge of neonatal danger signs was low in the study area. Mothers resided in an urban area, having antenatal follow-up, mothers who had got breastfeeding counselling, mothers who had got postnatal care counselling, multiparous mothers and good practice of essential neonatal care were factors associated with maternal knowledge of neonatal danger signs. Therefore, healthcare workers should encourage mothers to have antenatal follow-up and provide postnatal care counselling regarding key neonatal danger signs before discharge from the health facilities.